Penerapan pembelajaran kitab Akhlaq Lilbanin terhadap tata krama santri - Rosita, Siti (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
Etiquette education is an important aspect in the moral development of students at Islamic boarding schools. This study aims to examine the effectiveness of teaching the Kitab Akhlaq Lilbanin in shaping the etiquette of 7th grade students at the Daarul Uluum Islamic Boarding School. The scope of the study covers the learning process, strategies, and their impact on the daily behavior of students. The method used is qualitative research with a case study approach, through observation, interviews, and documentation. The data is analyzed using triangulation to ensure the validity and reliability of the results. The results show that around 60% of students have successfully demonstrated an increase in polite and civilized behavior, in accordance with the values taught. The application of methods including lectures, question and answer sessions, and exemplary examples from ustadz proved to be effective in shaping the character and manners of santri in a sustainable manner. In conclusion, the teaching of kitab Akhlaq Lilbanin is an important instrument in the moral development and good behavior of santri, supported by a consistent and disciplined approach. Abstrak Pendidikan tata krama merupakan aspek penting dalam perkembangan moral siswa di sekolah asrama Islam. Penelitian ini bertujuan untuk mengkaji efektivitas pengajaran Kitab Akhlaq Lilbanin dalam membentuk etika siswa kelas 7 di pondok pesantren Daarul Uluum. Ruang lingkup penelitian mencakup proses pembelajaran, strategi, dan dampaknya terhadap perilaku sehari-hari siswa. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan studi kasus, melalui observasi, wawancara, dan dokumentasi. Data dianalisis menggunakan triangulasi untuk memastikan validitas dan reliabilitas hasil. Hasil menunjukkan bahwa sekitar 60% siswa berhasil menunjukkan peningkatan perilaku sopan dan beradab, sesuai dengan nilai-nilai yang diajarkan. Penerapan metode termasuk ceramah, sesi tanya jawab, dan contoh teladan dari ustadz terbukti efektif dalam membentuk karakter dan sopan santun santri secara berkelanjutan. Kesimpulannya, pengajaran kitab Akhlaq Lilbanin merupakan alat penting dalam pengembangan moral dan perilaku baik santri, didukung oleh pendekatan yang konsisten dan disiplin.